2019
DOI: 10.1002/pc.25484
|View full text |Cite
|
Sign up to set email alerts
|

High mechanical and tribological performance of polyimide nanocomposite reinforced by fluorinated graphene oxide

Abstract: Novel polyimide/fluorinated graphene oxide (PI/FGO) nanocomposites with outstanding mechanical, thermal, and tribological properties were obtained using FGO nanosheets which were successfully fabricated by simple hydrothermal reaction. FGO exhibited distinguished interface adhesion with PI matrix due to covalent bonds, resulting improved mechanical and wear resistance of PI/FGO nanocomposites. Wherein, PI/FGO‐0.5 nanocomposite demonstrated conspicuous tribological performance accompanied with 33.1% decrease of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Also, it reduced the CoF values and improved wear resistance (PI; B-o-D; the counterpart is the GCr15 steel ball with a diameter of 3 mm; R a = n/d; frequency = 5 Hz; P = 10 N; t = 30 min; DSF, SLF). Min, C., et al designed the ‘PI + 0.5 wt.% FGO’ nanocomposite [ 56 ]. Due to covalent bonds, the great FGO to PI interfacial adhesion increased their mechanical strength and wear resistance.…”
Section: Point Contactsmentioning
confidence: 99%
“…Also, it reduced the CoF values and improved wear resistance (PI; B-o-D; the counterpart is the GCr15 steel ball with a diameter of 3 mm; R a = n/d; frequency = 5 Hz; P = 10 N; t = 30 min; DSF, SLF). Min, C., et al designed the ‘PI + 0.5 wt.% FGO’ nanocomposite [ 56 ]. Due to covalent bonds, the great FGO to PI interfacial adhesion increased their mechanical strength and wear resistance.…”
Section: Point Contactsmentioning
confidence: 99%
“…Wherein, the addition of FG signicantly enhanced the lubrication performance of pure PI, and its friction coefficient and wear rate were reduced by 33.1% and 80.8%, respectively. 44 These ndings indicate that FG is an potential material in the coating eld. However, the formation process of FG leads to a change in the hybrid orbital of graphene from sp 2 to sp 3 , which might be causing FG with different microstructure under different uorine contents.…”
Section: Introductionmentioning
confidence: 96%
“…The strong adherence of GO to the PEEK resulted in an in situ-formed GO coating and prevented scratching from the steel counterpart. Min et al [114] reported a novel fluorinated GO/polyimide (FGO/PI) nanocomposite via simple hydrothermal reactions (Fig. 10).…”
Section: Go-based Fillers In a Matrix Of Frictional Pairsmentioning
confidence: 99%